Cafeteria diet increases liquid intake and serum creatinine levels in rats - Ströher, Roberta; Macedo, Isabel Cristina de; de Oliveira, Carla; Scarabelot, Vanessa Leal; Rizzo, Tizye Lima; Goularte, Jeferson Ferraz; Caumo, Wolnei; Klein, Adriane Belló; Sanvitto, Gilberto Luiz; Torres, Iraci LS (Clinical and Biomedical Research, 2017)
Introduction: Important changes in human dietary pattern occurred in recent decades. Increased intake of processed foods leads to obesity, which is related with the development of chronic diseases such as type 2 diabetes mellitus, hypertension, as well as cardiovascular and chronic kidney diseases. The prevalence of hypertension has also dramatically increased in recent years, and high sodium intake contributes to this scenario. In healthy individuals, kidneys are the primary end-organs that regulate sodium homeostasis. This study aims to evaluate renal function parameters and systolic blood pressure measurements in an animal model of obesity. Methods: Sixty-day-old male Wistar rats (n=30) were divided into two groups: standard (SD) and cafeteria diet (CD). Cafeteria diet was altered daily and was composed by crackers, wafers, sausages, chips, condensed milk, and soda. All animals had free access to water and chow and the experiment was carried out for 6 weeks. Weight gain, sodium and liquid intake control, systolic blood pressure measurements, and renal function parameters were evaluated. Results: Animals exposed to cafeteria diet had an increase of 18% in weight compared to the control group. Sodium intake was increased by cafeteria diet and time (F(1,28)= 773.666, P=0.001 and F(5,28)= 2.859, P=0.02, respectively) and by the interaction of both factors (F(6,28)= 2.859, P=0.02). On liquid intake occurred only effect of cafeteria diet and time (F(1,28)= 147.04, P=0.001 and F(5,28)=3.996, P=0.003, respectively). Cafeteria diet exposure also induced an increase on creatinine serum levels (P=0.002), however this effect was not observed on creatinine urine levels (P>0.05) nor on systolic pressure measurements (Students’ t test, P>0.05). Conclusions: Obesity induced by cafeteria diet exposure increases liquid intake and alters creatinine serum levels, an important renal function marker. Considering the high consumption of hypercaloric food currently in the world, further studies are required to elucidate the modifications on renal function triggered by this diet over time. Key-words: Hypertension; kidney; renal function; obesity; hypercaloric diet